Quality attributes of fresh pineapple-mango juice blend during storage - Shamsudin, Rosnah; Zulkifli, N. A.; Kamarul Zaman, A. A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2020)
Blending or mixing two or more of fruit juices is able to improve the quality of juices as compared to single flavour. Pineapple and mango are among the popular tropical fruits in Malaysia. Despite the massive production of pineapple in Malaysia, utilisation of pineapple as a juice remains unpopular due to its exotic and strong flavour. Blending of pineapple with mango is believed to overcome this issue. Nevertheless, suitable blending ratios play important role in the end product quality. The present work aims to determine the physicochemical and nutritional quality of fresh blended pineapple-mango juice at different blending ratios for 25 days of refrigerated storage (4 ± 2°C). Physicochemical (colour, pH, titratable acidity, and total soluble solid) and nutritional (vitamin C, total phenolic content, and total antioxidant content) properties of fresh pineapple-mango juice blends of ratio 80% pineapple with 20% mango (R80:20) and 50% pineapple with 50% mango (50:50) were determined throughout 25 days of storage. Pineapple-mango juice blends at blending ratio of R80:20 exhibited better qualities in term of colour (lightness, chroma, hue, and browning index), chemical composition, and nutritional content.